Faça no seu ritmo mas não perca a hora: tomada de decisão sob demandado usuário utilizando dados da Web - Silva, Manoela Camila Barbosa da (Universidade Federal de São Carlos, 2017)
In the current knowledge age, with the continuous growth of the web data volume and where business decisions must be made quickly, traditional BI mechanisms become increasingly inaccurate in order to help the decision-making process. In response to this scenario rises the BI 2.0 concept, which is a recent one and is mainly based on the Web evolution, having as one of the main characteristics the use of Web sources in decision-making. However, data from Web tend to be volatile to be stored in the DW, making them a good option for situational data. Situational data are useful for decision-making queries at a particular time and situation, and can be discarded after analysis. Many researches have been developed regarding to BI 2.0, but there are still many points to be explored. This work proposes a generic architecture for Decision Support Systems that aims to integrate situational data from Web to user queries at the right time; this is, when the user needs them for decision making. Its main contribution is the proposal of a new OLAP operator, called Drill-Conformed, enabling data integration in an automatic way and using only the domain of values from the situational data.In addition, the operator collaborates with the Semantic Web, by making available the semantics-related discoveries. The case study is a streamings provision system. The results of the experiments are presented and discussed, showing that is possible to make the data integration in a satisfactory manner and with good processing times for the applied scenario.
Take your time, but don´t be late: on-demand decision-making using web data
Keywords: Tecnologia OLAP; OLAP technology; Web semântica; Self-Service BI; Dados transitórios; Integração de dados (Computação); Data integration (Computer service); Semantic Web; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO